Forging American communism : the life of William Z. Foster - Johanningsmeier, Edward P., 1956- (Princeton legacy library, 1994)
A major figure in the history of twentieth-century American radicalism, William Z. Foster (1881-1961) fought his way out of the slums of turn-of-the-century Philadelphia to become a professional revolutionary as well as a notorious and feared labor agitator. Drawing on private family papers, FBI files, and recently opened Russian archives, this first full-scale biography traces Foster's early life as a world traveler, railroad worker, seaman, hobo, union activist, and radical journalist, and also probes the origins and implications of his ill-fated career as a top-echelon Communist official and three-time presidential candidate. Even though Foster's long and eventful life ended in Moscow, where he was given a state funeral in Red Square, he was, as portrayed here, a thoroughly American radical. The book not only reveals the circumstances of Foster's poverty-stricken childhood in Philadelphia, but also vividly describes his work and travels in the American West. Also included are fascinating accounts of his early political career as a Socialist, "Wobbly," and anarcho-syndicalist, and of his activities as the architect of giant organizing campaigns by the American Federation of Labor, involving hundreds of thousands of workers in the meatpacking and steel industries. The author views Foster's influence in the American Communist movement from the perspective of the history of American labor and unionism, but he also offers a realistic assessment of Foster's career in light of factional intrigues at the highest levels of the Communist International. Originally published in 1994. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905